Nexus Between Financial Events and Emotional Exhaustion: Mediating Roles of Deliberate Thinking and Negative Interpersonal Events - Yang, Liwei (Frontiers in Psychology, 2022)
Financial stress and emotional exhaustion have become prevalent elements of modern society, especially after COVID-19. This pandemic has changed people's lives, dominantly in a negative way. Individuals have begun to face the stress and emotional exhaustion associated with particular financial stressor events. However, only limited studies have analyzed the relationship between financial stressor events and emotional exhaustion to date. Therefore, the current study aims to explore the relationship between different financial stressor events in an individual's life and emotional exhaustion based on their well-being. This study also identifies the variables that play a mediating role in assessing the relationship between emotional exhaustion and financial stressor events. To achieve this, the researcher collected data from employees working in large organizations in May 2021 and December 2021. The study employs path analysis to assess the relationship between the identified variables. The study found that both organizations and employees are directly affected by financial stress, leading to emotional exhaustion or a decline in the mental well-being of the individuals. In addition, the study also found that financial stress and emotional exhaustion can directly affect the physical health of individuals. The study further revealed that deliberate thinking, negative interpersonal events, and individual characteristics are some of the identified variables that act as mediators between financial stressor events and emotional exhaustion.